Bioadsorben Campuran Kulit dan Tongkol Jagung untuk Menurunkan Kadar BOD Limbah Batik - Miftakhul Jannah; Ferry Kriswandana; Marlik; Iva Rustanti Eri Wardojo (Window of Health : Jurnal Kesehatan, 2022)
Liquid waste from batik industry often causes environmental problems, because there is a pollutant content of Biochemical Oxygen Demand (BOD). Corn cobs and husks contain high cellulose which has the potential to become activated carbon. This study aims to analyze the bioadsorbent mixture of cobs and corn husks in reducing BOD levels in batik wastewater. This type of research is pre-experimental, the research design is One Group Pretest Posttest Design. Variations in the mass of bioadsorbent mixture of corn cobs and husks with a ratio of (70:30), (60:40) and (50:50) contact time for 2.5 hours in 500 ml of batik liquid waste. Measurement of BOD levels was carried out after treatment. Data analysis using ANOVA test. The highest percentage of decrease in BOD levels after treatment was in the mass variation of 38 gr: 25 gr (60:40) 81.79% and the decrease value was 9243 mg/L. BOD levels before treatment using a mixture of cob and corn husk bioadsorbent were 11300 mg/L and after treatment it was 2057 mg/L which means that there is 1 pair of variations in the mass of the mixture of corn cobs and husks in reducing the average different BOD content in batik wastewater. Bioadsorbent mixture of cobs and corn husks can reduce BOD levels in batik wastewater.